2005
DOI: 10.1152/physrev.00020.2004
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Cell Behavior Electrically: Current Views and Future Potential

Abstract: Direct-current (DC) electric fields are present in all developing and regenerating animal tissues, yet their existence and potential impact on tissue repair and development are largely ignored. This is primarily due to ignorance of the phenomenon by most researchers, some technically poor early studies of the effects of applied fields on cells, and widespread misunderstanding of the fundamental concepts that underlie bioelectricity. This review aims to resolve these issues by describing: 1) the historical cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
922
1
15

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 896 publications
(950 citation statements)
references
References 209 publications
12
922
1
15
Order By: Relevance
“…Thus, it is conceivable that the external application of a microcurrent could normalize the endogenous electrical gradient, either by influencing the existing current gradient or by triggering protein activation to induce favourable cellular responses 30. Initial evidence showing that electrical signals can modulate kinase activity was reported in a paper published by Zhao and colleagues in Nature 31.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is conceivable that the external application of a microcurrent could normalize the endogenous electrical gradient, either by influencing the existing current gradient or by triggering protein activation to induce favourable cellular responses 30. Initial evidence showing that electrical signals can modulate kinase activity was reported in a paper published by Zhao and colleagues in Nature 31.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that endogenous electric fields play a role in regeneration, and it has been shown that applied electric fields are able to enhance regeneration and repair in vertebrates (Borgens et al, 1977(Borgens et al, , 1981Kerns and Lucchinetti, 1992;McCaig et al, 2005). have recently demonstrated a molecular link between electric currents and tail regeneration in Xenopus.…”
Section: Electric Currents and Regenerationmentioning
confidence: 99%
“…Thus, functional GJC is dependant on the existence of compatible hemichannels on the cells' surfaces, the permeability of the hemichannels to the substance, and the open status of the gap junction. Regulated GJC paths serve to establish patterns of iso-potential and/or iso-pH cell fields (Sherman and Rinzel, 1991;Fitzharris and Baltz, 2006;Rocheleau et al, 2006); this epigenetic "prepattern" overlaid upon the embryonic morphology, working in concert with the molecular fields defined by gene expression domains, is an important control element in embryonic patterning (Levin, 2003a;Nuccitelli, 2003;McCaig et al, 2005). This extremely versatile system for communication allows for rapid synchronization among cells in a tissue and the passage of signals, both of which can be regulated at many levels.…”
Section: Behavior Is Dependent Upon Gap Junction (Gj) -Mediated Signalsmentioning
confidence: 99%